2015
DOI: 10.1016/j.visres.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The effective reference frame in perceptual judgments of motion direction

Abstract: The retinotopic projection of stimulus motion depends both on the motion of the stimulus and the movements of the observer. In this study, we aimed to quantify the contributions of endogenous (retinotopic) and exogenous (spatiotopic and motion-based) reference frames on judgments of motion direction. We used a variant of the induced motion paradigm and we created different experimental conditions in which the predictions of each reference frame were different. Finally, assuming additive contributions from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Previously, we have shown that the perceived motion of a target stimulus can be influenced by nearby motion of another object, and that this object need not be surrounding the target stimulus, as in the induced-motion paradigm (Agaoglu et al, 2015;Noory et al, 2015). In this study, we started off by replicating our previous findings that each local motion vector has a reference field associated with it, and this is manifested by increased illusory percepts of backward motion with decreasing distance to this moving reference frame.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Previously, we have shown that the perceived motion of a target stimulus can be influenced by nearby motion of another object, and that this object need not be surrounding the target stimulus, as in the induced-motion paradigm (Agaoglu et al, 2015;Noory et al, 2015). In this study, we started off by replicating our previous findings that each local motion vector has a reference field associated with it, and this is manifested by increased illusory percepts of backward motion with decreasing distance to this moving reference frame.…”
Section: Discussionmentioning
confidence: 51%
“…The fields created by different motion vectors interact in order to determine a motion vector that will serve as the reference frame at a given point and time in space. Previously, we have demonstrated the field-like nature-that is, the distance-dependent influence-of motion-based reference frames in the perception of motion direction (Agaoglu, Herzog & Öğmen, 2015;Öğmen et al, 2013). This concept of distancedependent reference-frame determination is also consistent with earlier observations of relative motion.…”
Section: Reference-frame Metric Field (Rfmf) Theorymentioning
confidence: 92%
See 1 more Smart Citation
“…For example, the point lights placed on a person in the biological motion paradigm (Johansson, 1973) creates a very complex stimulus; however, by grouping these points into a meaningful Gestalt (Yantis, 1992), the visual system is capable of computing a common reference frame, which can be used to simplify the relative motions of various point lights. Several studies showed that when the stimulus allows grouping of parts, motion groupings based nonretinotopic reference frames (relative motion) account for perceived direction of motion (Agaoglu et al, 2015a(Agaoglu et al, , 2015bBoi, Öğmen, Krummenacher, Otto, & Herzog, 2009;Duncker, 1929Duncker, /1938Johansson, 1973;Noory et al, 2015). In fact, Agaoglu et al (2015b) quantified the contributions of retinotopic, spatiotopic, and relative-motion reference frames and showed that relative motion dominated both during fixation and SPEM, with a contribution more than 80% when the distance between the stimuli was 2 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that when the stimulus allows grouping of parts, motion groupings based nonretinotopic reference frames (relative motion) account for perceived direction of motion (Agaoglu et al, 2015a(Agaoglu et al, , 2015bBoi, Öğmen, Krummenacher, Otto, & Herzog, 2009;Duncker, 1929Duncker, /1938Johansson, 1973;Noory et al, 2015). In fact, Agaoglu et al (2015b) quantified the contributions of retinotopic, spatiotopic, and relative-motion reference frames and showed that relative motion dominated both during fixation and SPEM, with a contribution more than 80% when the distance between the stimuli was 2 degrees. The dominance of the relative motion decreased with the distance between stimuli; however, for separations as large as 11 deg, the contribution of relative motion was still substantial (60%).…”
Section: Discussionmentioning
confidence: 99%